PENGARUH RELEVANSI NILAI INFORMASI LABA DAN ALIRAN KAS TERHADAP HARGA SAHAM DALAM KAITANNYA DENGAN SIKLUS HIDUP PERUSAHAAN - Fatmasari, Khairunisa, Mariana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
This study was conducted to see the effect of earnings and cash flow to the stock price. Companies that usted in Indonesian Stock Exchange (ISE) has a different life cycle. The life cycle consists of four stages : start-up, growth, mature and decline. Different life cycle in a vary companies effect the level of earnings and cash flow generated by the company. This study uses financial data of all companies listed on the Indonesian Stock Exchange (ISE) from 2003-2013. This research is using multiple regression analysis. Earnings, operating cash flow, investing cash flow, financing cash flow as an independent variable and stock price as the dependent variable. This research also tested the hypothesis that consists of simultaneous testing and partial testing. The significance level used in this study by 5%. This study found that stock price on the company in the start-up stage is not effected by earnings and cash flow. In the growth stage, the stock price is effected by earnings and operating cash flow. In the mature stage, the stock price is influenced by earnings. In the last stage which is decline stage, the stock price is effected by the investing cash flow. As a conclusion, this research shows that earnings and cash flow have a different effectin each company life cycle. Keywords : Earnings, Cash Flow, Stock Price, Life Cycle